SETRATEGI MARKETING BMT MASLAHAH CABANG MARON DALAM MENINGKATKAN LABA SELAMA PANDEMI COVID-19 - Norhayati Norhayati; Cici Widya Prasetyandari; Ainur Rofiq Sofa (Jurnal Imagine, 2022)
Bitul Maal wat Tamwil (BMT) is a sharia-based financial institution based on the principle of sharia, not applying interest in the transaction, but with the results agreed on between BMT and the customer. In general terms, the main activities of BMT are the same as banking in general, therefore BMT must implement a good strategy to face business competition during the Covid-19 pandemic. The study aims to identify the marketing strategies used by the BMT Maslahah Maron branch to increase revenue during the covid-19 pandemic. The method of research used is qualitative research. Data collection techniques by way of interviews, observation and documentation. Studies have shown that the marketing strategy used is an approach to people with a fetch system.